2006
DOI: 10.1080/10826080600846219
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Needle Sharing: Meta-Analyses of Social Context Risk Behaviors of Injection Drug Users Attending Needle Exchange Programs

Abstract: This study gathered data from U.S. and international needle exchange programs (NEPs). Of particular interest were outcome measures of dependent variables related to behaviors within social contexts of injection drug users (IDUs), an area not well understood. Thirty-one studies, with a total of 86 separate measures of 36 dependent variables were included. Because combining all results into a single meta-analysis would be inappropriate, dependent variables were placed into five categories for five separate meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Lastly, we observe that the results of this investigation are consistent with studies in the US and other countries focused on social networking and peer groups (Emerson et al 2005;Ksobiech 2006;Von Lengerke et al 2004). It is clear that those associated with a particular FCSW, whether manager or peer, significantly influence the behavior of the FCSW.…”
Section: Discussionsupporting
confidence: 89%
“…Lastly, we observe that the results of this investigation are consistent with studies in the US and other countries focused on social networking and peer groups (Emerson et al 2005;Ksobiech 2006;Von Lengerke et al 2004). It is clear that those associated with a particular FCSW, whether manager or peer, significantly influence the behavior of the FCSW.…”
Section: Discussionsupporting
confidence: 89%
“…Racial/ethnic group disparities in HIV infection among people who inject drugs (PWID) are particularly important, for several reasons: HIV, injecting drug use and racial/ethnic minority group membership are all stigmatized in many different cultures . Stigmatization may lead to higher stress among PWID, followed by anxiety and depression , followed by higher rates of risk behavior . The stigmatization of drug use may lead community leaders of both majority and minority communities to fail to acknowledge drug use in minority communities and thus not provide appropriate services . Mistrust between racial/ethnic minority and majority communities may generate conflict that impedes implementation of HIV prevention programs for PWID, particularly for controversial issues such as needle exchange programs . The higher rates of HIV infection among racial/ethnic minority PWID are generally not explained by high rates of risk behaviors. Minority PWID tend to report equal or lower rates of injecting risk behavior compared to racial/ethnic majority PWID .…”
Section: Introductionmentioning
confidence: 99%
“…As the context often varies, factors influencing risky behaviors may vary by gender. 31,32 Whereas research on gender differences in descriptive and injunctive norms among IDUs is scarce, several studies examining the role of perceived norms in sexual behavior has indicated that normative influence varies by gender. Buunk et al reported that descriptive norms predicted intention to use condoms for male and female heterosexual adults.…”
Section: Introductionmentioning
confidence: 99%